2015
DOI: 10.1155/2015/519190
|View full text |Cite
|
Sign up to set email alerts
|

Kingella kingaeCausing Septic Arthritis of the Knee in anImmunocompetentAdult

Abstract: The bacterium Kingella kingae is a species of Gram-negative coccobacillus usually found in the oropharynx. This is an emerging pathogen reported to cause bacteraemia, endocarditis, and osteoarticular infections in children and endocarditis in the immunocompromised adult. However, there are few cases of isolated joint infections reported in the immunocompetent adult. Due to specific isolation techniques required, delay in diagnosis can compromise patient outcome. We report a rare case of septic arthritis of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…kingae usually causes septic arthritis in early childhood (1), but has been rarely reported in adults; only 10 such cases were identified in a literature review by using PubMed, Google, and Google Scholar and the words "Kingella kingae," "adult," and "arthritis." Previous reports included both male and female patients, of the entire adult age range, and in both immunosuppressed and immunocompetent patients (3)(4)(5)(6)(7)(8). Other reported rare infections with K. kingae in adults include peritonitis (9), keratitis (10,11), stomatitis (12), urinary tract infection (13), and bacteremia (14).…”
Section: Resultsmentioning
confidence: 99%
“…kingae usually causes septic arthritis in early childhood (1), but has been rarely reported in adults; only 10 such cases were identified in a literature review by using PubMed, Google, and Google Scholar and the words "Kingella kingae," "adult," and "arthritis." Previous reports included both male and female patients, of the entire adult age range, and in both immunosuppressed and immunocompetent patients (3)(4)(5)(6)(7)(8). Other reported rare infections with K. kingae in adults include peritonitis (9), keratitis (10,11), stomatitis (12), urinary tract infection (13), and bacteremia (14).…”
Section: Resultsmentioning
confidence: 99%
“…Yagupsky described osteoarticular infection as the most common manifestation of invasive K. kingae infection, occurring in 62.4 % (53 of 85) of cases among children in a large referral center in Israel from 1988 to 2002 [ 1 ]. The first case of K. kingae native joint septic arthritis in an otherwise healthy adult was described by Esteve et al in 2001 [ 3 ], with a second case described by Ricketts et al in 2015 [ 4 ]; both cases involved the knee. A review of the English language literature demonstrates cases of K. kingae osteoarticular infection in adults with severe rheumatoid arthritis with Felty’s syndrome [ 5 ] and recent upper respiratory infection [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The optimal antimicrobial treatment duration for K. kingae septic arthritis is even less understood, owing to the inherent rarity of the condition. Previous cases of K. kingae septic arthritis in adults were successfully treated with anywhere from 10 days to 3 months of oral or parenteral antibiotics, with or without surgical washout [ [3] , [4] , [5] , [6] ]. Our patient was successfully treated with surgical debridement and four weeks of ceftriaxone, with improvement in both clinical symptoms as well as laboratory values.…”
Section: Discussionmentioning
confidence: 99%
“…The "H" represents Haemophilus; the "A" represents Aggregatibacter, previously Actinobacillus; the "C" represents Cardiobacterium; the "E" represents Eikenella; and the "K " represents Kingella. Each of these microorganisms can also cause pyogenic arthritis [5][6][7][8][9][10][11]. A recently published review of native joint septic arthritis found members of the HACEK group to be the primary pathogen in 27 of 436 (6.2%) infected native joints [12].…”
Section: Introductionmentioning
confidence: 99%